Character Building Through Online Learning Using A Mobile Gadget At A Junior High School In Medan, Indonesia - Purba, Risdo Sappetua; Hutauruk, Desinora Natalia; Situmeang, Diancrisy; Mode, Aninda Nesya; Pratama, Reza (Jurnal Pendidikan Ilmu Sosial, 2021)
This study aims to find out what influences students’ character building. In addition, this study examines the various problems faced by students, teachers, and parents during the pandemic in relation to the policies decreed by the Ministry of Education, Republic of Indonesia, regarding application of online learning as the most effective way to solve problems during the covid-19 pandemic. This research also provides solutions to overcome the problems that raised, namely the roles of gadget which can shape the character of students so that the implementation of education is better. This is considering that the benefits of character education are not only for students as individuals, but they are as a group as well as their families, social environment, and their future.